Postoperative Analgesia Time in Dogs Submitted to Mastectomy and Anesthetized with Tumescent Solutions of Lidocaine or Ropivacaine - Del Lama Rocha, Fabiana; Nunes, Newton; Chiconi Dacunto dos Santos, Paula; Kazuo Ido, Cléber; do Espírito Santo Silva, Paloma; Simões Azenha Aidar, Eveline; Amaral da Silva, Helen Roberta; Carmagnani Prada, Tiago (Acta Scientiae Veterinariae, 2020)
Background: Mastectomy, a procedure with high pain stimulation, is the treatment of choice for bitches with breast cancer. Tumescent anaesthesia is widely used for transoperative and postoperative analgesia in bitches submitted to mastectomy, because facilitates tissue divulsion, also contributing significantly for the rapid recovery of patients. Although, there is no consensus as to which local anesthetic to use and at what concentration it should be used. Herein was investigated which local anesthetics, lidocaine or ropivacaine, when used in tumescent solutions, could provide a more lasting analgesic effect in the postoperative period in bitches submitted to radical unilateral mastectomy. Materials, Methods & Results: Sixteen bitches were sedated with chlorpromazine (0.3 mg/kg) and meperidine (3 mg/kg) followed by anesthesia with propofol and isofluorane. Then, bitches were randomly assigned to two groups (n= 8 each): LG group, infused with 15 mL/kg of tumescence solution containing 0.1% lidocaine; and RG group, infused with 15 mL/kg of tumescence solution with 0.1% ropivacaine. The study was conducted in a double-blind fashion. Control group did not include, because the patients would be submitted to severe or unbearable pain, according to the short-form of the Glasgow pain Scale (CMPS-SF). The heart (HR) and respiratory (ƒ) rates, and systolic blood pressure (SBP) were measured in the pre-operative period and immediately after extubation (Mextub) and at 0.5 h, 1 h, 2 h, 4 h, 8 h, and 12 h after the extubation. Analgesic efficacy was assessed using the CMPS-SF and von Frey filaments. Both groups showed higher means for HR at 0.5 h (167 ± 7 in LG; 170 ± 7 in RG) than at 4 h (117 ± 7 in LG; 120 ± 7 in RG). CMPS-SF revealed higher medians (P= 0.038) at the Mextub and 12 h time points for the LG [5 (3-6) and 1 (0-2)] than for the RG [5 (2-5) and 0 (0-1)]. Discussion: Pain was excluded as a possible explanation for the difference presented for HR in both groups because, moderate pain is considered when more than two cardiorespiratory parameters show an increase of at least 20% in relation to baseline values, which did not occur in this study. Indeed, most animals were walking at 0.5 h after extubation and, in many cases, this occurred before the collection of data for the postoperative period. This may have influenced the results since exercise releases catecholamines and increases HR. Moreover at 4 h after extubation, most animals were asleep. As metabolism decreases during sleep, expected that HR would also decrease and that was indeed the case. Regarding CMPS-SF, the way the patients walks was the item that most contributed to the high score found for the Mextub time point because it’s impossible to be performed seconds after extubation. As the reluctance to move occurred only immediately after extubation, the values obtained at the Mextub time point are more likely to be due to an anesthetic residual effect and not to the pain stimulus itself. When the groups were compared, the median values obtained at the LG were greater than RG at the Mextub and 12 h postoperative time points. There was no need for analgesic rescue differing from those in literature that reported the need for analgesic rescue in 50% of the animals. Those study established a CMPS-SF score of 3.3 as indicative for analgesic rescue whereas our research established a score of 7. Tumescence solutions with lidocaine or ropivacaine provide equivalent postoperative analgesia for at least 12 h.